Kinetic Characteristics of Oil Natural Antioxidants - Radzievska, I.G.; Melnyk, O.P. (Science and Innovation, 2024)
Oxidation parameters of sunflower, maize, walnut, palm, and palm kernel oils have been defined by Tsepalov`s graphical and DPPH methods. The influence of the oil natural antioxidants and the degree of unsaturation of fatty acids on the oxidation rate has been showed. The methods can be used to predict the oil oxidation stability in the course of storage.